PREVENTION OF TRESPASSER ACCESSING IN NETWORKS USING TICKET GRANTING SERVICE (International Journal of Engineering and Computer Science, 2013)
This paper addresses the problem of protecting the system from non trusted users access the policy share. Web site administrators routinely rely on IP-address blocking for disabling access to misbehaving users, but blocking IP addresses is not practical if the abuser routes through an anonym zing network. As a result, administrators block all known exit nodes of anonym zing networks, denying anonymous access to misbehaving and behaving users alike. To address this problem, we present Nymble, a system in which servers can ―blacklist‖ misbehaving users, thereby blocking users without compromising their anonymity. The interactive counterparts of group signatures are identity escrow schemes or group identification scheme with revocable anonymity. This work introduces a new provably secure group signature and a companion identity escrow scheme that are significantly more efficient than the state of the art. In its interactive, identity escrow form, our scheme is proven secure and coalition-resistant under the strong RSA and the decisional Diffie-Hellman assumptions.